2021
DOI: 10.1016/j.fertnstert.2021.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal acetate compared with leuprorelin acetate for Japanese women with symptomatic uterine fibroids: a phase III randomized controlled trial

Abstract: Objective: To evaluate the efficacy and safety of ulipristal acetate (UPA) for uterine fibroids (UFs), a phase III study was conducted with leuprorelin (LEU) as a comparator. This is the first confirmatory trial of UPA for UFs among Asians. Design: Multicenter, randomized, double-blind, double-dummy, parallel-group study. Setting: Thirty-two sites in Japan. Patient(s): Patients were assigned to 2 arms, with 82 patients in the UPA group and 79 patients in the LEU group. Intervention(s): In the UPA group, 10 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
16
1
1
Order By: Relevance
“…The rates of patients with amenorrhea for 35 days (92%-97%) and uterine bleeding normalization (99%-100%) in this study were similar to the rates for the 10-mg dose in the long-term European PEARL study (35-day amenorrhea: 80%-90%, uterine bleeding normalization: 89%-94%), 13 the 12-week Japanese dosefinding study (35-day amenorrhea: 88%, uterine bleeding normalization: 96%), 17 and the 12-week Japanese randomized trial (35-day amenorrhea: 87%, uterine bleeding normalization: 95%). 18 However, compared with the long-term PEARL study (50%-72% reduction), a lower percentage change in fibroid volume was reported in the current study (20%-35% reduction). Although no formal assessment of fibroid volume and UPA response between European and Japanese women has been conducted, it is possible that racial differences may have contributed to the differences in the reduction in fibroid volume between these studies.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The rates of patients with amenorrhea for 35 days (92%-97%) and uterine bleeding normalization (99%-100%) in this study were similar to the rates for the 10-mg dose in the long-term European PEARL study (35-day amenorrhea: 80%-90%, uterine bleeding normalization: 89%-94%), 13 the 12-week Japanese dosefinding study (35-day amenorrhea: 88%, uterine bleeding normalization: 96%), 17 and the 12-week Japanese randomized trial (35-day amenorrhea: 87%, uterine bleeding normalization: 95%). 18 However, compared with the long-term PEARL study (50%-72% reduction), a lower percentage change in fibroid volume was reported in the current study (20%-35% reduction). Although no formal assessment of fibroid volume and UPA response between European and Japanese women has been conducted, it is possible that racial differences may have contributed to the differences in the reduction in fibroid volume between these studies.…”
Section: Discussioncontrasting
confidence: 85%
“…In the leuprorelin comparative study in Japanese women, incidences of hot flush were lower in the UPA group than in the leuprorelin group. 18 In January 2021, the EMA recommended restricting the use of 5-mg UPA because of rare events of severe liver injury that have been reported women who had used 5-mg UPA. 16 In the current study, eight women experienced hepatic treatmentemergent AEs that were considered related to UPA.…”
Section: Discussionmentioning
confidence: 99%
“…/L, 350 × 10 9 /L, 400 × 10 9 /L, 450 × 10 9 /L, 500 × 10 9 /L, and 550 × 10 9 /L was 53 4,. 56.7, 60.0, 63.2, 66.3, 69.2, 72.0, 74.6, 77.1, 79.4, and 80.1%, respectively (Figure…”
mentioning
confidence: 94%
“…Up to 25% of women and up to 30-40% of women older than 40 years have clinical symptoms of uterine fibroids (1)(2)(3). Many patients show clinical symptoms such as menorrhagia, irregular bleeding, pelvic pain, or infertility (4)(5)(6), which have a significant negative effect on their quality of life. Currently, the management for uterine fibroids includes surgery, medicine, uterine artery embolization (UAE), radiofrequency ablation (RFA), ultrasound-guided high-intensity focused ultrasound (USgHIFU), and magnetic resonance-guided high-intensity focused ultrasound (MRgHIFU) (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these trials demonstrated dose-response differences between the 5-and 10-mg treatment groups. This issue of racial differences in response to ulipristal acetate is further explored by Osuga et al (4) in an Asian population in this issue of Fertility and Sterility.…”
mentioning
confidence: 99%